PELAKSANAAN PROGRAM PENGUATAN SISTEM INOVASI DAERAH (PSIDa) OLEH BADAN PENELITIAN DAN PENGEMBANGAN PROVINSI RIAU TAHUN 2017 - Oktaviana, Nurul; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Law Number 23 Year 2014 concerning Regional Government has substance in innovating for Regional Government as the basis for developing effective, efficient and participatory public services. In accordance with the Minister of Research and Technology and Minister of Home Affairs Regulation Number 03 of 2012 and Number 36 of 2012 concerning Strengthening the Regional Innovation System, BPPD has a central role in driving the strengthening of the innovation system in the region. Balitbang Riau Province has the task of helping the Governor carry out the functions of supporting government affairs which are the regional authority in strengthening the regional innovation system. The formulation of the problem in this study is (1) how is the implementation of the regional innovation system strengthening program (PSIDa) by the Riau Province Research and Development Agency in 2017? (2) what are the inhibiting factors in implementing the regional innovation system strengthening program (PSIDa) by the Riau Province Research and Development Agency in 2017?. This study aims to (1) describe the implementation of the regional innovation system strengthening program (PSIDa) by the Riau Province Research and Development Agency in 2017, (2) describe the inhibiting factors in implementing the regional innovation system strengthening program (PSIDa) by the Research and Development Agency Province of Riau in 2017. This research is a descriptive study with a qualitative approach. The location of this research was conducted at the Riau Province Research and Development Agency. Data collection techniques carried out were through interviews and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and conclusions. The results of the study concluded that the implementation of the regional innovation system strengthening program (PSIDa) by the Riau Province Research and Development Agency in 2017 was viewed through aspects of communication, resources, disposition, and bureaucratic structures that were not fully optimal. The implementation of the Regional Innovation System Strengthening Program by Riau Province Balitbang still needs to improve the quality and quantity of functional researchers and engineering officials, increase the portion of the budget in stages, increase operational support capacity, and improve coordination, socialization and understanding of regional innovation system strengthening program policies.Keywords: Strengthening Regional Innovation Systems, Implementation of Policies, and Regional Innovations